Parental smoking related to adenoidectomy and tonsillectomy in children. Issue 2 (June 1978) - Said, G; Zalokar, J; Lellouch, J; Patois, E
Abstract : Histories of adenoïdectomy and tonsillectomy were ascertained, as well as smoking habits of both parents, using questionnaires answered by 3920 schoolchildren aged 10 to 20. Adenoïdectomy and/or tonsillectomy, considered as an index of repeated upper respiratory tract disease in early childhood, was very significantly related to the amount of smoking by each parent. This relationship persisted when age, sex, day nursery attendance, sibship size, and history of appendicectomy were controlled.